Sistem Presensi Siswa berbasis Internet of Things menggunakan Sensor Sidik Jari pada SMK Perhotelan 45 Mataram - Baiq Rizki Putri Utami; I Wayan Agus Arimbawa; Fitri Bimantoro (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
Fingerprint is one of the unique part of human body that can be used as a personal identity with the help of fingerprint biometric technology to help identify it. The use of fingerprint biometric technology can be a solution for student attendance that helps minimize errors or fraud such as manipulation or falsification in the process of recording attendance. The application of computerized attendance recording can be done by utilizing the concept of the Internet of Things (IoT) which assumes that electronic devices can be connected to each other to communicate or exchange data independently through internet networks that using protocols to communicate, including the MQTT (Message Queue Telemetry Transport protocol), which is lightweight message and designed for devices with limited resources. Therefore, an Internet of Things based attendance system was created by utilizing fingerprint sensor technology on the MQTT protocol to assist schools in improving attendance recording performance, as well simplifying the process of recording student attendance at SMK Perhotelan 45 Mataram which still applies conventional attendance recording procedure. The fingerprint enroll process is carried out with a system interface in the form of a web application using the MQTT protocol. Fingerprint feature data is stored on the fingerprint sensor memory module. The total time used to record attendance for 10 respondents is 11,241 seconds with the average time obtained is 1.1241 seconds. It was found that 50% of users agreed to the application of the internet-based fingerprint presence system based on MOS testing.